Processo de institucionalização no sistema informacional de custos e tratamento do desperdício em uma entidade hospitalar - Santos, Keila Priscila dos (2017)
The objective of this study was to analyze the process of institutionalization of the cost and waste treatment system at the Ministro Costa Cavalvanti Hospital in the city of Iguassu Falls, state of Paraná, Brazil, following the model of Burns and Scapens (2000). Therefore, a descriptive study was conducted, a case study procedure and a qualitative-quantitative approach. The selected case corresponded to a hospital that already implemented the SIC in the year 2008 and it is currently discussing the issues. Data collection was done through interviews, documents, field observations and surveys. For the qualitative analysis, content analysis was applied for the interpretation of the results, with the help of technological tools: Atlas TI® and Nvivo® and for the quantitative descriptive and frequency statistical part, using SPSS® software. The main results indicate that the SIC passed through the coding and incorporation stage, being in the reproduction phase, not yet occurring the institutionalization of the management tool. As a theoretical contribution of the study, we highlight the understanding of the factors present in the institutionalization process, as well as institutionalization difficulties.